2014
DOI: 10.1016/j.foodchem.2014.05.103
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of antioxidant extraction from Solanum tuberosum potato peel waste by surface response methodology

Abstract: This study reports the optimised conditions (temperature, ethanol concentration and processing-time) for antioxidant extraction from potato peel (Agria variety) waste. At short extraction times (34 min), optimal yields of phenolic (TP) and flavonoid (Fv) compounds were reached at 89.9°C and ethanol concentrations of 71.2% and 38.6%, respectively. The main phenolic compounds identified in the extracts were chlorogenic (Cl) and ferulic (Fer) acids. A significant positive correlation was found between antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 33 publications
7
82
3
2
Order By: Relevance
“…However, peels are the main residues of potato processing which present up to 3% -5% causing many environmental problems [8]. PP is a good source of natural antioxidants [9] [10], phenolic compounds [8] [11] [12] especially purple potato variety "Russet" [13]- [16] and fibers [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, peels are the main residues of potato processing which present up to 3% -5% causing many environmental problems [8]. PP is a good source of natural antioxidants [9] [10], phenolic compounds [8] [11] [12] especially purple potato variety "Russet" [13]- [16] and fibers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Authors were looking for optimisation options for extraction conditions (temperature, duration time, used concentration of ethanol) using a surface response methodology, when ethanol serves as an environmentally friendly alternative to organic solvents. Results of this study showed that potato peel has great antioxidant abilities, which can be used to limit oxidation [18].…”
Section: Biotechnologiesmentioning
confidence: 80%
“…Antioxidant extraction from potato peels has been studied in [18] as well. Authors were looking for optimisation options for extraction conditions (temperature, duration time, used concentration of ethanol) using a surface response methodology, when ethanol serves as an environmentally friendly alternative to organic solvents.…”
Section: Biotechnologiesmentioning
confidence: 99%
“…The Brazilian production of potato, Solanum tuberosum, is one of the largest in the world (Amado et al, 2014, Brazinskiene et al, 2014 with an area of about 130,000 ha and a production of three million tons (FAO, 2013). This plant has a relatively shallow root system (Neumann et al, 2012) requiring large inputs of nutrients, especially nitrogen, to maintain productivity and tuber quality (Tein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%